Incidence and Risk Factors Affecting Development of Perianal Fistulas after Drainage of Perianal Abscesses - Omar Mohammad Khalil; Labib Al Ozaibi; Hadiel M. Kaiyasah; Nour AlDeen Hejazi (Dubai Medical Journal)
Background: Perianal fistulas can present significant morbidity and detriment to a patient’s quality of life. This study aimed to quantify the incidence of perianal fistulas and attempted to identify any risk factors for their development. Materials and Methods: This retrospective study reviewed all patients who underwent drainage of first-time perianal abscesses in Rashid Hospital from 2014 to 2018. Noncryptoglandular causes of fistula formation were excluded after which incidence and risk factors were investigated. Results and Discussion: A total of 445 records were reviewed of which 131 met the inclusion criteria (103 males and 28 females). The median age of patients was 37 with ranges of 15–85. There was no statistically significant finding relating to gender (p value = 1.00), smoking (p value = 1.00), location of perianal abscess (p value = 0.347), and postoperative antibiotics (p value = 0.694). There was no statistically significant finding relating to patients below or above 40 (p value = 0.846), and logistic regression testing revealed no statistical significance in age relating to development of perianal fistulas. There was a 13.2% increased proportion of nondiabetics to develop perianal fistulas as compared to diabetics (32 vs. 19%), but it was not found to be statistically significant (p value = 0.236). Conclusion: None of the risk factors studied were found to be statistically significant in the development of perianal fistulas after drainage of perianal abscesses and the incidence was found to be 29.8%.